2015 IEEE Power &Amp; Energy Society Innovative Smart Grid Technologies Conference (ISGT) 2015
DOI: 10.1109/isgt.2015.7131877
|View full text |Cite
|
Sign up to set email alerts
|

Real-time state estimation of the EPFL-campus medium-voltage grid by using PMUs

Abstract: Abstract-We describe the real-time monitoring infrastructure of the smart-grid pilot on the EPFL campus. We experimentally validate the concept of a real-time state-estimation for a 20 kV active distribution network. We designed and put into operation the whole infrastructure composed by the following main elements: (1) dedicated PMUs connected on the medium-voltage side of the network secondary substations by means of specific current/voltage transducers; (2) a dedicated communication network engineered to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
98
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 16 publications
(18 reference statements)
0
98
0
Order By: Relevance
“…With our implementation, we have shown that iPRP can support several sessions between hosts without any significant delay or processing overhead. We have made our implementation publicly available and are currently installing it in our campus smart-grid [11].…”
Section: Implementation and The Diagnostic Toolkitmentioning
confidence: 99%
“…With our implementation, we have shown that iPRP can support several sessions between hosts without any significant delay or processing overhead. We have made our implementation publicly available and are currently installing it in our campus smart-grid [11].…”
Section: Implementation and The Diagnostic Toolkitmentioning
confidence: 99%
“…Our implementation is publicly available and is currently being installed in our campus smart-grid [6]. In the future, we intend to do extensive measurements on our smart-grid and study the performance of iPRP in real networks.…”
Section: B Processing Overhead Caused By Iprpmentioning
confidence: 99%
“…Failure to satisfy these constraints can result in economic losses or, even worse, human lives can be endangered in cases when these failures affect safety mechanisms. Notable examples of such applications (often built on top of cyber-physical systems) are process-control and emergencymanagement applications in the oil and gas industry [1], realtime detection of pollutants in the water/wastewater industry [2], vehicle-collision avoidance in car industry [3], automatic train control [4], process control in chemical industry [5], state estimation in smart grid [6], high-frequency trading [7] and distributed online gaming [8].…”
mentioning
confidence: 99%
“…RESULTS AND DISCUSSION The framework is tested in simulation to verify its ability to dispatch the operation of a monitored distribution feeder of the EPFL campus [11]. The available power consumption measurements are split into daily sequences and used to determine the day-ahead power consumption forecast and the advertised power consumption profile.…”
Section: A Day-ahead Of Operationmentioning
confidence: 99%